FACILITY LAYOUT REDESIGN AT DEPARTMENT OF RAILWAY INFRASTRUCTURE (CASE STUDY AT PT PINDAD BANDUNG) - Tri Puja Kurnia; Whydiantoro Whydiantoro; Tantri Wahyuni (Jurnal Mekanika dan Manufaktur, 2021)
Every company, both large companies and small companies, will face problems layout.semua facilities for the production of both machines, labor and other facilities should be provided in place of each, so that it can work with baik.setiap array of machines and production equipment at a factory called layout. So layout problems associated with the preparation of machinery and equipment production in pabrik.perosoalanya is how we set up the machines and other production equipment so that it can run production as effectively as possible. The composition of plant equipment. The layout in PT. PINDAD (Persero) shall be designed so that the development of efficient factory area and the production and distribution process can proceed smoothly, so the security, safety, and comfort for employees can be met. In addition to the process equipment, some engine placement should match the flow of the production process e-clip, and so placed on the part that does not interfere with the traffic of goods and processes. Location of the plant will directly affect the survival of plant process includes the successful and smooth production plant.